eCM 2017
DOI: 10.22203/ecm.v034a21
|View full text |Cite
|
Sign up to set email alerts
|

Sustained intra-cartilage delivery of low dose dexamethasone using a cationic carrier for treatment of post traumatic osteoarthritis

Abstract: Disease-modifying osteoarthritis drugs (DMOADs) should reach their intra-tissue target sites at optimal doses for clinical efficacy. The dense, negatively charged matrix of cartilage poses a major hindrance to the transport of potential therapeutics. In this work, electrostatic interactions were utilised to overcome this challenge and enable higher uptake, full-thickness penetration and enhanced retention of dexamethasone (Dex) inside rabbit cartilage. This was accomplished by using the positively charged glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 74 publications
2
65
0
Order By: Relevance
“…Although significant systemic side effects were noted in the animals that received repeated injections of DEX, these studies have all demonstrated a protective capacity of DEX in the preservation of joint tissues in the short term. Others have also described successes in the treatment of PTOA using IA DEX in ACL deficient rabbit models, as well as using triamcinolone acetonide in the knees of ACL transected Yorkshire pigs . A clinical study is currently underway to investigate the efficacy of IA DEX in the management of distal radius fractures to prevent PTOA of the wrist …”
mentioning
confidence: 99%
“…Although significant systemic side effects were noted in the animals that received repeated injections of DEX, these studies have all demonstrated a protective capacity of DEX in the preservation of joint tissues in the short term. Others have also described successes in the treatment of PTOA using IA DEX in ACL deficient rabbit models, as well as using triamcinolone acetonide in the knees of ACL transected Yorkshire pigs . A clinical study is currently underway to investigate the efficacy of IA DEX in the management of distal radius fractures to prevent PTOA of the wrist …”
mentioning
confidence: 99%
“…[42] This interesting result is however mitigated by the detrimental influence of Avidin itself on GAGs, hypothesized by the authors. [30] In comparison, chitosan is a much stronger binder due to its significantly higher net charge and partitioning coefficient. Consequently, the retention time and efficacy of chitosan-dex are expected to be significantly higher, while having high biocompatibility and low cell toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…[23,29] Improved infiltration, suppression of injury-induced joint swelling and catabolic gene expression could be shown when injecting Avidin-dex intra-articularly in a posttraumatic OA rabbit model. [30] Although providing strong binding, electrostatic interactions are rather unspecific and could lead to off-target delivery. In parallel, we focused on developing a more specific approach by using a collagen type II-binding peptide.…”
Section: Introductionmentioning
confidence: 99%
“…This gradient allows continued diffusion and further transport of the P4-phage into the tumor tissue than observed with the control-phage. The difference in concentration gradients resulting in improved tissue uptake has been observed in cartilage explants [80][81][82] and mucus hydrogels 63 . Data represents mean ± SD (n=3).…”
Section: Effect Of Surface Chargementioning
confidence: 94%